1997
DOI: 10.1021/jf960583p
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Capacity of Wine on Human LDL Oxidation in Vitro:  Effect of Skin Contact in Winemaking of White Wine

Abstract: To assess the antioxidative effect of the non-alcoholic components of wine, human low-density lipoprotein (LDL) was oxidized in vitro by copper ions in the presence of polyphenolic extracts from three wines:  standard red wine (R), standard white wine (W1), and white wine the must of which had been in contact with grape solids during 8 h before fermentation (W2). Lipoprotein peroxidation was monitored as the formation of conjugated dienes, of thiobarbituric acid reactive substances (TBARS), and fluorescent sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Our results confirm a variation in phenolic content among wine samples tested. These results are in agreement with those available in the literature (Campodonico, Barberi, Pizarro, Sotomayor, & Lissy, 1998;Frankel, Waterhouse, & Teissedre, 1995;Hurtado et al, 1997;Kanner, Frankel, Granit, German, & Kinsella, 1995;Sato et al, 1996;Simonetti, Pietta, & Testolin, 1997). The presence of high concentrations of gallic acid in red wines would be expected since this phenolic acid is principally formed by hydrolysis of flavonoid gallate esters, which are largely absent in white wines, due to the lack of skin extraction.…”
Section: Total Phenol Contentsupporting
confidence: 91%
“…Our results confirm a variation in phenolic content among wine samples tested. These results are in agreement with those available in the literature (Campodonico, Barberi, Pizarro, Sotomayor, & Lissy, 1998;Frankel, Waterhouse, & Teissedre, 1995;Hurtado et al, 1997;Kanner, Frankel, Granit, German, & Kinsella, 1995;Sato et al, 1996;Simonetti, Pietta, & Testolin, 1997). The presence of high concentrations of gallic acid in red wines would be expected since this phenolic acid is principally formed by hydrolysis of flavonoid gallate esters, which are largely absent in white wines, due to the lack of skin extraction.…”
Section: Total Phenol Contentsupporting
confidence: 91%
“…It has been pointed out that certain hydroxycinnamates (eg caffeic and p ‐coumaric acids) are less effective antioxidants compared with certain flavonoids (eg quercetin),26–28 but other investigations have indicated that caffeic acid and its derivatives may be potent inhibitors of LDL in vitro oxidation 29–32. Similar results have been reported 33.…”
Section: Discussionmentioning
confidence: 65%
“…While there are reports in the literature about the concentration of polyphenols in white wines, mainly obtained using HPLC-DAD (Okamura and Watanabe 1981;Hurtado et al 1997;Budić-Leto and Lovrić 2002;Jeffery et al 2008), still there are no data on phenolics in white wines from the Republic of Macedonia. Therefore, it was considered that determination of total phenolics, total flavonoids, and total flavan-3-ols in white wines from the Smederevka and Chardonnay varieties, produced with two doses of SO 2 and two yeasts would be of great importance for obtaining a general overview of their phenolic content and their changes during aging.…”
Section: Introductionmentioning
confidence: 99%